Estimation of Some Immunological and Physiological Parameters for Obese Human - Amera Kamal Mohammed (Journal of Global Pharma Technology, 2017)
Adipose tissue expansion during obesity is associated with inducing Proinflammatory and inflammatory cytokine responses, decreasing insulin sensitivity, type 2 diabetes mellitus and dyslipidemia. The objective of this study was to determine some humeral immune levels including, serum IL-1βand C-reactive protein (CRP) as well as blood glucose and lipid profile as physiological criteria. Blood samples were collected after an overnight fast from a group of obese (n = 48)and none- obese (41) as a control group depending on BMI withwaist circumference with age ranged between (20-40 year).The results revealed that significant increase (P≤ 0.05) in mean of BMI(Kg/M2) ,WC (cm), CRP (ng/mL), FBG (mmol/L), total cholesterol(mmol/L)and , low density lipoprotein (mmol/L), while there is no significant difference in the levels of IL-1β (pg/mL), triglyceride(mmol/L), high-density lipoprotein (mmol/L) and very low density lipoprotein (mmol/L) among obese individuals compared with control group , and depending on the sex of the study groups the results showed that significant increase (P≤ 0.05) in means of BMI(Kg/M2) , WC (cm), IL-1β (pg/mL), FBG (mmol/L) ,while there is no significant difference in means of CRP (ng/mL), TC(mmol/L) , LDL(mmol/L), TG(mmol/L), HDL(mmol/L) and VLDL(mmol/L). The data demonstrated that the three classes of obesity had higher significant differences (P≤ 0.05) in means of BMI (Kg/M2), WC (cm), and CRP (ng/mL), FBG (mmol/L), TC (mmol/L) and, LDL (mmol/L).Keywords: Obesity, Type 2 diabetes, Insulin resistance, Immunity, Inflammation.